2019
DOI: 10.1021/acs.nanolett.9b02226
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Detection with Lightguiding Nanowires: Determination of Protein Concentration and Diffusivity in Supported Lipid Bilayers

Abstract: Determining the surface concentration and diffusivity of cell-membrane-bound molecules is central to the understanding of numerous important biochemical processes taking place at cell membranes. Here we use the high aspect ratio and lightguiding properties of semiconductor nanowires (NWs) to detect the presence of single freely diffusing proteins bound to a lipid bilayer covering the NW surface. Simultaneous observation of light-emission dynamics of hundreds of individual NWs occurring on the time scale of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Intriguingly, we find indications that both aerotaxy and epitaxy nanowires light up already upon single-molecule binding, consistent with earlier results. 27 This becomes apparent when correlating the number of bright nanowires with the brightness of each nanowire as function of analyte concentration ( Figure 5 ). For both types of nanowires, we can distinguish three concentration regimes, which we assign as follows: (I) At the lowest analyte concentrations, the intensity per nanowire is more or less constant, while the number of bright nanowires increases.…”
Section: Resultsmentioning
confidence: 94%
“…Intriguingly, we find indications that both aerotaxy and epitaxy nanowires light up already upon single-molecule binding, consistent with earlier results. 27 This becomes apparent when correlating the number of bright nanowires with the brightness of each nanowire as function of analyte concentration ( Figure 5 ). For both types of nanowires, we can distinguish three concentration regimes, which we assign as follows: (I) At the lowest analyte concentrations, the intensity per nanowire is more or less constant, while the number of bright nanowires increases.…”
Section: Resultsmentioning
confidence: 94%
“…In the context of optical biosensor applications, semiconductor nanowires have been mostly explored on the basis of their higher surface area compared with planar substrates, but they have recently gained increased attention also due to their highly advantageous optical properties [ 13 , 14 , 15 ]. Specifically, nanowires have been shown to collect the fluorescence emission of a large number of surface-bound fluorophores and re-emit it at their tip, not unlike an optical fiber [ 16 ], thereby greatly enhancing the overall intensity of the emission and even enabling single-molecule detection without advanced optics [ 17 ]. In addition to the effect of the increased surface area offered by the nanowires, which increases the total fluorescence signal within the field-of-view, the signal is furthermore enhanced due to a combination of advantageous physical effects: (i) the relatively high refractive index of semiconductor nanowires enables them to support waveguide modes at small diameters, collecting and guiding the emission from fluorophores placed in immediate proximity to the nanowire surface [ 16 , 18 ]; (ii) it has been suggested that the coupling of excitation light in waveguide modes can increase the intensity of the local electromagnetic field close to the nanowire’s surface, enhancing the excitation of fluorophores placed in their close proximity [ 19 , 20 ]; and (iii), the emission of light from the nanowire tip can be highly directional, thereby increasing the light collection efficiency of the readout system.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, some investigated the physical interactions between nanowires and fluorescent dyes suitable for biomolecular labeling [ 15 , 16 , 18 , 20 ], for example showing how guiding efficiency is strongly dependent on nanowire material, diameter, and light wavelength, with different diameters maximizing efficiency for a certain wavelength range, allowing optimization for selected fluorophores [ 16 ]. Others explored their use for investigating biological systems, such as molecular motors [ 14 ], supported lipid bilayers [ 17 ], and live cells [ 19 ]. Patterned arrays of spatially ordered ZnO nanowires have been used for protein microarray applications, demonstrating detection limits in the fM regime, even beating state-of-the-art ELISA platforms when applied both on human samples and serum spiked with carefully controlled biomarker concentrations [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, strategies for the controllable synthesis of nanowires with respect to their morphology, size, and crystal phase have been significantly developed . These advances facilitate fundamental research related to their electrical, photonic, optoelectronic, and mechanical properties (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 To date, strategies for the controllable synthesis of nanowires with respect to their morphology, size, and crystal phase have been significantly developed. [27][28][29][30][31] These advances facilitate fundamental research related to their electrical, photonic, optoelectronic, and mechanical properties ( Figure 1). The physical relevance between a specific functionality and nanowire characteristics can accordingly be possibly acquired.…”
Section: Introductionmentioning
confidence: 99%